2018
DOI: 10.1371/journal.pone.0200254
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life, neuropsychiatric symptoms and structural brain changes in clinically isolated syndrome

Abstract: BackgroundNeuropsychiatric symptoms and reduced health-related quality of life (HRQoL) are frequent in multiple sclerosis, where are associated with structural brain changes, but have been less studied in clinically isolated syndrome (CIS).ObjectiveTo characterize HRQoL, neuropsychiatric symptoms (depressive symptoms, anxiety, apathy and fatigue), their interrelations and associations with structural brain changes in CIS.MethodsPatients with CIS (n = 67) and demographically matched healthy controls (n = 46) un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…Thus, (1) platelet entry into the CNS parenchyma was identified prior to any detectable CD4 + cells in blood, lymphoid organs and the CNS and (2) platelet–neuron associations with concomitant generation of a pro-inflammatory environment and functional disturbance were demonstrated in regions where CD3 cells or lesions are never observed (retina) [25], or remain minimal (hippocampus and spinal cord grey matter) [25,41] over the disease trajectory. This scenario would also be consistent with the early occurrence of depression in MS, which often precedes presentation [36,37,38,39,40].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Thus, (1) platelet entry into the CNS parenchyma was identified prior to any detectable CD4 + cells in blood, lymphoid organs and the CNS and (2) platelet–neuron associations with concomitant generation of a pro-inflammatory environment and functional disturbance were demonstrated in regions where CD3 cells or lesions are never observed (retina) [25], or remain minimal (hippocampus and spinal cord grey matter) [25,41] over the disease trajectory. This scenario would also be consistent with the early occurrence of depression in MS, which often precedes presentation [36,37,38,39,40].…”
Section: Discussionsupporting
confidence: 75%
“…The observations of extensive hippocampal demyelination [32] coupled with significant decreases in synaptic density together with reduced expression of proteins specific for neuronal function including memory and learning are of interest, because of the association of this structure with emotion and cognition [35] and the evidence of depression and cognitive defects in MS patients [36,37,38]. Indeed, the significance of these symptoms as primary manifestations of the disease rather than consequences of living with a chronic disease has gained momentum over the last decade [39,40]. Prior investigations of hippocampal pathology in MOG 35–55 -induced EAE in our laboratory [41] revealed a complex pattern of damage, with minor inflammation in the dorsal hippocampus, moderate inflammation in the ventral region of the structure, but severe inflammation in the fimbrium region.…”
Section: Introductionmentioning
confidence: 99%
“…Less research has been done on the impact of anxiety on cognitive performance in early MS. Although six studies did not find a significant relationship, 16 , 30 , 85 , 113 , 142 , 147 five studies 26 , 45 , 74 , 98 , 107 showed that greater anxiety symptomatology was associated with worse performance on aspects of executive functioning, working memory, processing speed, immediate structured verbal learning (ie, story memory), and delayed structured verbal memory. Simioni et al 125 also found a higher prevalence of anxiety among persons with cognitive involvement.…”
Section: Resultsmentioning
confidence: 90%
“…While depression is prevalent in MS, 163 there is mixed evidence on its relationship with cognitive functioning. Ten studies did not find an association between performance and level of depressive symptom severity, 29 , 34 , 37 , 46 , 83 , 85 , 113 , 124 , 135 , 141 while 14 studies found a negative impact, 16 , 18 , 22 , 30 , 44 , 45 , 69 , 70 , 74 , 98 , 105 , 107 , 125 , 142 such as higher levels of depression among persons with cognitive impairment or worse performance on verbal fluency, aspects of executive functioning, multitasking, working memory, and processing speed tasks. There is also mixed evidence with quality of life and cognition, with two studies not finding a relationship 82 , 115 and four studies noting a significant association.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation